2008
DOI: 10.2166/wst.2008.513
|View full text |Cite
|
Sign up to set email alerts
|

A pilot-scale comparison of mesophilic and thermophilic digestion of source segregated domestic food waste

Abstract: This is a revised personal version of the text of the final journal article, which is made available for scholarly purposes only, in accordance with the journal's author permissions. The full citation is: Banks, C.J., Chesshire, M. and Stringfellow A. (2008 ABSTRACT Source segregated food waste was collected from domestic properties and its composition determined together with the average weight produced per household, which was 2.91 kg per week. The waste was fed over a trial period lasting 58 weeks to an ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
30
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(38 citation statements)
references
References 10 publications
7
30
0
1
Order By: Relevance
“…In the current study the detrimental effects of ammonia appeared to become evident at around 2500 mg N l -1 (FAN ~1100 mg N l -1 ). This is below the inhibitory TAN concentration observed in mesophilic digesters operating on the same substrate [1], but corresponds to the FAN inhibition threshold found e.g. by Hansen et al [24].…”
Section: Overall Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…In the current study the detrimental effects of ammonia appeared to become evident at around 2500 mg N l -1 (FAN ~1100 mg N l -1 ). This is below the inhibitory TAN concentration observed in mesophilic digesters operating on the same substrate [1], but corresponds to the FAN inhibition threshold found e.g. by Hansen et al [24].…”
Section: Overall Discussionsupporting
confidence: 61%
“…Early digestion trials with this material, however, showed accumulation of volatile fatty acids (VFA) over extended run times in both mesophilic and thermophilic digestion systems [1]. Similar observations were made in a full-scale thermophilic digester treating source segregated restaurant and catering waste [2], and in the UK Government's food waste demonstration AD plant in Ludlow, UK [3]; and have also been demonstrated in laboratoryscale digesters [4,5].…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…This is comparable to the 92% of volatile matter content obtained from the kitchen waste from Burford, Shropshire [11]. Wastes with high volatile matter content produce more biogas if digested properly, as it is the organic matter that produces biogas.…”
Section: B Ash Contentsupporting
confidence: 60%
“…It has been reported on a number of occasions that digestion at high ammonia concentrations can give stable biogas production at alkaline pH over extended periods of time under continuous loading conditions. In digesters treating food waste these conditions can also lead to operation at elevated levels of volatile fatty acids in the digestate (Banks et al, 2008, Neiva Correia et al, 2008. Similar conditions have been reported in thermophilic cattle slurry digesters (Neilsen and Angelidaki, 2008), and in other nitrogen rich substrates such as slaughterhouse waste Wang, 1999, Wang andBanks 2003).…”
Section: Introductionmentioning
confidence: 99%